1987
DOI: 10.1007/bf00142696
|View full text |Cite
|
Sign up to set email alerts
|

Optic neuropathy from thiamine deficiency in a patient with ulcerative colitis

Abstract: A 35-year-old man with ulcerative colitis who was receiving parenteral feeding with large amounts of glucose, suddenly developed severe optic neuropathy and oculomotor palsy. The visual acuity fell bilaterally to 0. Although it was stated that thiamine has been regularly supplemented in the preceding period, high doses of vitamin B1 were given. Visual acuity promptly returned to 1.0 but large visual field defects persisted. Later on it appeared that erroneously no vitamin B1 has been given before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…Both cases had thiamine defi ciency induced by parenteral nutrition. Similar to our case, Van Noort et al [7] reported total visual loss with partial recovery after thiamine supplementation in WE. Sometimes, in WE visual acuity may also be normal despite optic neuropathy [8] .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Both cases had thiamine defi ciency induced by parenteral nutrition. Similar to our case, Van Noort et al [7] reported total visual loss with partial recovery after thiamine supplementation in WE. Sometimes, in WE visual acuity may also be normal despite optic neuropathy [8] .…”
Section: Discussionsupporting
confidence: 76%
“…Ocular manifestations of WE generally include nystagmus, ophthalmoplegia and very rarely visual deterioration and optic neuropathy. We found only two cases of optic neuropathy in nonalcoholic patients in the literature [7,8] . Both cases had thiamine defi ciency induced by parenteral nutrition.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although many cases of WErelated to intravenous fluid therapy have been reported in Japan, no case referred to ONor impaired visual acuity. In the literature, van Noort et al reported a case of ONfrom thiamine deficiency induced by parenteral nutrition with large amounts of glucose (4 …”
mentioning
confidence: 99%
“…The central nervous system is almost completely dependent on glucose metabolism for energy2,3 and is therefore susceptible to thiamine deficiency. Classically, thiamine deficiency manifests as the triad of Wernicke encephalopathy: acute confusional state, ataxia, and ophthalmoparesis 4.…”
Section: Introductionmentioning
confidence: 99%